تأثير التسميد الورقي بعنصري البوتاسيوم والكالسيوم في نمو وحاصل ومكونات الماش / EFFECT OF FOLIAR APPLICATION WITH POTASSIUM AND CALCIUM ELEMENTSIN SOME GROWTH AND YIELD CHARACTERS OF GREEN GRAM (Vigna radita L.) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
The experiment was conducted on the private farm in Al-mussiabMasshroaa regions during Summer seasons 2016 to study the effect of  foliar application by 4 concentration  of potassium (0, 100,200,300) mgk.L-1  and 4 concentration of calcium (0,50,100,200) mgCa .L-1  and interaction on growth  and yield of green gram .  Randomized complete block design (RCBD) with three replications was used .The results showed that the level 200 mg K.L-1 giving the highest average height plant , plant dry weight ,pods number ,seed number and seeds yield for plantwhile dominance the concentration 100mg K.L-1 on the seed 1000 weight character, Casprayed had no significant on seed yield